Efficient Capacity Provisioning for Firms with Multiple Locations: The Case of the Public Cloud - Hummel, Patrick; Schwarz, Michael (EC'22, 2022)
This paper presents a model in which a firm with multiple locations strategically chooses capacity and prices in each location to maximize efficiency. We find that the firm provisions capacity in such a way that the probability an individual customer will be unable to purchase the goods the customer desires is lower in locations with greater expected demand. The firm also sets lower prices in larger locations. Finally, we illustrate that it is more efficient to direct customers who are willing to go to multiple locations to locations with greater expected demand.